2021
DOI: 10.1186/s12891-020-03912-z
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal pathology as an early warning sign of systemic amyloidosis: a systematic review of amyloid deposition and orthopedic surgery

Abstract: Background Transthyretin and immunoglobulin light-chain amyloidoses cause amyloid deposition throughout various organ systems. Recent evidence suggests that soft tissue amyloid deposits may lead to orthopedic conditions before cardiac manifestations occur. Pharmacologic treatments reduce further amyloid deposits in these patients. Thus, early diagnosis improves long term survival. Questions/purposes The primary purpose of this systematic review was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 54 publications
(54 reference statements)
0
20
0
Order By: Relevance
“…As patients could potentially present with musculoskeletal conditions prior to systemic manifestations, orthopaedic surgeons may play a role in early diagnosis. 43 Hearing impairment was even more frequent than CTS in our patients (n = 22; 55% versus n = 17; 42.5%). ATTR-related hearing loss is already known, although there is little in the literature on the subject.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…As patients could potentially present with musculoskeletal conditions prior to systemic manifestations, orthopaedic surgeons may play a role in early diagnosis. 43 Hearing impairment was even more frequent than CTS in our patients (n = 22; 55% versus n = 17; 42.5%). ATTR-related hearing loss is already known, although there is little in the literature on the subject.…”
Section: Discussionmentioning
confidence: 51%
“…ATTR and AL are difficult diseases to diagnose due to non‐specific symptoms, overlapping diagnoses and under‐recognition by physicians. As patients could potentially present with musculoskeletal conditions prior to systemic manifestations, orthopaedic surgeons may play a role in early diagnosis 43 …”
Section: Discussionmentioning
confidence: 99%
“…The presence of amyloidosis and its typing has also been systematically searched for in biopsies of common orthopedic surgeries regardless of the demonstration of systemic amyloidosis. Wininger et al in a large systematic review of amyloid deposition in patients undergoing lumbar spinal decompression found the presence of ATTR on 64/157 (41%) surgical specimens [ 35 ]. In two different studies, the thickness of the ligamentum flavum was found to be significantly greater in patients with LSS and ATTR positive biopsy than in those with negative biopsy.…”
Section: Lumbar Spine Stenosismentioning
confidence: 99%
“…Later studies using NMR analysis further confirmed this hypothesis [ 6 ]. Due to the ubiquitous presence of proteins in the body’s cells, amyloidosis is clinically considered a systemic disease [ 7 ]. For example, amyloid accumulation plays a special role in the pathogenesis of Alzheimer disease (AD), Parkinson’s disease, or transthyretin amyloidosis [ 8 ].…”
Section: Amyloid Plaques Structure Importance Factors Predisposing To Their Appearancementioning
confidence: 99%